Analysis and optimization of piston engine exhaust noise silencer using ALLBEA NOISE - R. E. Dadashov; A. A. Chernousov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
This study presents a computational method for reducing exhaust noise in a two-stroke piston engine. The exhaust system was analyzed using the ALLBEA software package, and its optimization was performed using the ALLBEA NOISE program. A comparison of the calculated engine performance with the optimized silencer and the stock exhaust system demonstrated a 17 dB reduction in sound pressure level at the exhaust outlet, with only a minor power loss (less than 3%) at the shaft speed of 5500 rpm.